Implementation of the Qur'an Recitation Program to Foster Religious Character Among Students at MTs Negeri 6 Sragen - Josania Alfina Khansa; Dartim Dartim (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
This study aims to analyze the implementation of the Qur'an recitation program in fostering students' religious character at MTs Negeri 6 Sragen. The study employed a qualitative descriptive approach. Data were collected through observation, in-depth interviews with Islamic Education teachers and students, and documentation. The findings indicate that the program's implementation consists of three stages: planning, implementation, and evaluation. During the planning stage, the school systematically arranges the schedule, objectives, and technical aspects. The implementation stage is conducted routinely every morning with teacher supervision, using methods such as qira'ati, tikrar, talaqqi, and muraja'ah. The evaluation stage is carried out through direct observation, communication with parents, teacher coordination, and indicators of Qur'an reading ability. The evaluation results show positive behavioral changes in some students, including improved discipline, politeness, and Qur'an reading habits, although the changes are uneven and more evident in reading ability than in overall character. The program has a positive impact but requires continuous development.